Settlement Analysis of Pipe Culvert Situated in Soft Clay Treated with Prefabricated Vertical Drains - Adamu Beyene Negesa (Advances in Civil Engineering)
Engineering structures built on soft and compressible soils are often subjected to a long-lasting consolidation settlement. It is difficult to achieve an acceptable level of consolidation during the first few years/days of operation. Similarly, the culvert structure provided at station km 159 + 112 of the Awash-Kombolcha-Hara Gebeya Railway Project, Ethiopia, was situated along the route traversing soft clay ground of significant thickness. For the intention of reducing consolidation time and lessening the precarious impact of the postconstruction settlement, the soft clay ground was treated with preloading and prefabricated vertical drains. However, the culvert structure is currently undergoing consolidation settlement with varying magnitudes. The vertical deformation of the culvert site is monitored using settlement gauges installed at the site. Monitoring of the site continued for 120 days to track the extent of ground deformation at the culvert site. However, because of environmental and technical factors like calibration and alignment errors, the settlement instrument readings may be exposed to uncertainties, which may probably affect the safety of the culvert structure. Hence, the study is primarily aimed at evaluating the field deformation performance of the culvert structure for 120 days of the consolidation period through numerical analysis and comparing the result with the site settlement monitoring data. The critical effect of wick drain and some key parameters (fill thickness and wick drain spacing) were also scrutinized. Finite element-based numerical modeling was conducted by using the 2D GeoStudio/SigmaW package, and the Modified Cam Clay Constitutive model was adopted. The conducted numerical analysis revealed that the finite element result has good agreement with the field settlement monitoring data with only 0.0305 m maximum deviation in which the numerical analysis result remained greater for majority of the consolidation time. It can also be inferred that granular fill thickness and wick drain spacing were the key parameters impacting the settlement of the culvert structure.